Current therapeutic options for low‐risk papillary thyroid carcinoma: Scoping evidence review. Issue 1 (30th September 2021) - Sanabria, Alvaro; Pinillos, Pilar; Lira, Renan B.; Shah, Jatin P.; Tufano, Ralph P.; Zafereo, Mark E.; Nixon, Iain J.; Randolph, Gregory W.; Simo, Ricard; Vander Poorten, Vincent; Rinaldo, Alessandra; Medina, Jesus E.; et al.
Abstract: Most cases of thyroid carcinoma are classified as low risk. These lesions have been treated with open surgery, remote access thyroidectomy, active surveillance, and percutaneous ablation. However, there is lack of consensus and clear indications for a specific treatment selection. The objective of this study is to review the literature regarding the indications for management selection for low‐risk carcinomas. Systematic review exploring inclusion and exclusion criteria used to select patients with low‐risk carcinomas for treatment approaches. The search found 69 studies. The inclusion criteria most reported were nodule diameter and histopathological confirmation of the tumor type. The most common exclusions were lymph node metastasis and extra‐thyroidal extension. There was significant heterogeneity among inclusion and exclusion criteria according to the analyzed therapeutic approach. Alternative therapeutic approaches in low‐risk carcinomas can be cautiously considered. Open thyroidectomy remains the standard treatment against which all other approaches must be compared.